Primerjava preddvorno-prekatne in sinhrone prekatne elektrostimulacije srca pri bolnikih s stalnimi srčnimi spodbujevalniki - Žižek, David (Medicinski razgledi, 2004)
VDD pacing systems are an alternative to DDD pacing systems in patients with atrioventricular (AV) block and normal sinus node function. Our study comparedatrial sensing, ventricular stimulation threshold, AV synchrony, ventricular lead impedance and quality of life in patients with VDD and DDD pacing systems. It was assumed that there are differences concerning electrostimulation and hemodynamic support between VDD and DDD pacing systems.Ninety-six patients with implanted VDD or DDD pacing systems were enrolled prospectively into our study in 2000. The obtained data was statistically analysed using Student's t-test for independent samples or Mann-Whitney's t-test for two independent samples. Atrial sensing was significantly lower with the VDD system compared to the DDD system, at implantation and at present evaluation (p < 0.001). The ventricular pacing threshold for the VDD system at implantation was significantly lower than for the DDD system (p < 0.02). At the present evaluation, there was no significantdifference between VDD and DDD systems (p = 0.49). AV synchrony wasstatistically lower with VDD systems compared to DDD systems (p < 0.001). The difference between the values of ventricular lead impedance at implantation and at the present evaluation was significantly lower for VDD systems compared to DDD systems (p < 0.001). The quality of life did not differ significantly between VDD and DDD pacing systems (p = 0.96). VDD pacingsystems are reliable and safe concerning electrostimulation. However, hemodynamic support is better with DDD pacing systems.
Keywords: Heart Block; Srce, blok; Cardiac Pacing, Artificial; Srčni spodbujevalec; Srčno vzpodbujanje, umetno; Methods; Pacemaker, Artificial; Zaznava; Perception; Čutni prag; Električna impedanca; Sensory Thresholds; Electric Impedance; Kvaliteta življenja; Heart Atrium; Srce, predvor; Heart Ventricle; Srčni prekat; srčne bolezni; Quality Of Life; srce; heart; srčni spodbujevalci; električna stimulacija